PENGARUH BAURAN PEMASARAN TERHADAP KEPUTUSAN PEMILIHAN MEREK PADA PEMBELIAN OBAT MAG BERMEREK - , Elisabeth Purnamasari Djuhadi ([Yogyakarta] : Universitas Gadjah Mada, 2014)
People who are suffered heartburn symptoms are going to buy heartburn OTC medicine. The public as consumers have to make decision for choosing one out of various brands when purchased medicine. This study aims to determine the effect of marketing mix attributes on brand choice in branded heartburn OTC drug purchases by consumer. The research method used is descriptive analytic method with cross sectional apporach using 100 respondents were taken by purposive sampling technique. Methods of data analysis using ANOVA test to determine the relationship between marketing mix variables with the brand selection variable. Results interpretation of respondents answer to the purchase of various brand of heartburn OTC drugs are : drugâs product is considered very good (mean score of 81,65), drugâs promotion is considered fairly (mean score of 50,97), drugâs price is considered good (mean score of 65,67), and drugâs distribution is considered very good (mean score of 80,07). Anova test results obtained from the marketing mix attributes do not have a relationship with brand selection as indicated by the p-value > 0,05, ie for the product (0,326), promotion (0,498), price (0,425), and distribution (0,467). Then the marketing mix did not affect significantly on the brand name selection by costumers, so the analysis to find out how much influence marketing mix attribute to brand selection is not done